Pengaruh Sistem Informasi Manajemen Terhadap Efisiensi Kinerja dan Daya Saing Organisasi - Nur Qori Aprila; Muhammad Irwan Padli Nasution (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of information technology demands organizations to operate more efficiently and competitively. One of the ways to achieve this is through the implementation of a Management Information System (MIS). This study aims to analyze the influence of MIS on organizational performance efficiency and competitiveness. The research method employed is descriptive qualitative, using a literature study approach by reviewing various scientific sources and relevant studies published within the last five years. The results indicate that the implementation of MIS improves work efficiency through fast, accurate, and integrated information management. Furthermore, MIS strengthens organizational competitiveness by enhancing adaptability, coordination, and decision-making processes. In conclusion, MIS plays a crucial role in supporting performance efficiency and building the organization’s competitive advantage in the digital era.